1995
DOI: 10.1089/acm.1995.1.57
|View full text |Cite|
|
Sign up to set email alerts
|

A Critical Analysis of Acupuncture in Pulmonary Disease: Efficacy and Safety of the Acupuncture Needle

Abstract: Criteria for therapeutic efficacy and safety include significant amelioration of symptoms and, ideally, cure (i.e., patients' belief in effective improvement of symptoms and quality of life, durable impact on symptoms, verifiable subjective and objective changes); improved patient management (e.g., diminishing, or ceasing medication, physiotherapy, and other interventions); safety for patient and practitioner and an acceptable side effect profile; cost-effectiveness of the therapy in practice and to teach to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…Acupuncture is one of the most popular of the alternative therapies. Some of the attractions stem from its long standing use in Chinese medicine and the avoidance of the side-effects of more conventional treatments for asthma such as corticosteroids and b 2 -agonist sympathomimetics [8]. Overall effect sizes (standardised differences between means) of magnitudes between 0.07 and 0.13 (95% CI -0.07-0.31) were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acupuncture is one of the most popular of the alternative therapies. Some of the attractions stem from its long standing use in Chinese medicine and the avoidance of the side-effects of more conventional treatments for asthma such as corticosteroids and b 2 -agonist sympathomimetics [8]. Overall effect sizes (standardised differences between means) of magnitudes between 0.07 and 0.13 (95% CI -0.07-0.31) were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…An aim of meta-analysis is to increase the number of patients in order to detect such moderate effects with clinical significance [11] but the integrated number of patients in the present meta-analysis was still below the size given by a conventional power requirement. Secondly, placebo points used in asthma trials seem to be active in pulmonary disease [8]. Thirdly, missing information was a considerable limitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 4 A review of 16 randomised controlled trials involving 2937 participants concluded that acupuncture is a safe and potentially effective intervention for patients with asthma and COPD. 5 We have previously demonstrated that respiratory function evaluated with Borg scale scores and the 6 min walking distance (6MWD) could be markedly improved with acupuncture in a prospective matched-pair trial that included patients treated with acupuncture and those receiving standard medication. 6 However, differences in the effect of acupuncture between subgroups classifi ed according to disease severity are unclear.…”
Section: Introductionmentioning
confidence: 99%